The Relationship of Family Support in Compliance with Treatment in Diabetes Mellitus Patients at Sentra Medika Cibinong Hospital in 2024 - Fany Koesmawaty; Elly, Elly; Ns. Ananda Patuh Padaallah; Aprilina Sartika (Jurnal Multidisiplin Sahombu, 2025)
Diabetes Mellitus is a metabolic disease characterized by increased blood glucose levels, known as hyperglycemia due to impaired insulin secretion and insufficiency of insulin function itself and can result in death or disability, and have a significant impact on the quality of life of sufferers. This study aims to identify the characteristics of respondents and provide a demographic overview of the relationship between family support in compliance with treatment in Diabetes Mellitus patients at Sentra Medika Cibinong Hospital. This study uses a cross-sectional quantitative research method and emphasizes the time spent measuring or observing dependent and independent variable data one by one on 62 samples from 160 populations in October to November at Sentra Medika Cibinong Hospital. Based on the Kolmogorov-Smirnov data normality test and the research obtained asymp.sig (2-tailed) of 0.576 or > 0.05 meaning that the data is normally distributed and based on the statistical analysis of the chi-square test shows that P-Value = 0.005 (P <alpa 0.05), then Ha is accepted which means that there is a relationship between high family support and increased compliance with care at Sentra Medika Cibinong Hospital. From the results of this study, data analysis and discussion, the purpose of the study has been answered, namely there is a relationship between family support and compliance with care in diabetes mellitus patients at Sentra Medika Cibinong Hospital in 2024. The results of this study are expected to provide input for Sentra Medika Cibinong Hospital in an effort to provide promotion to diabetes mellitus patients regarding the importance of maintaining compliance in carrying out self-care activities.